马油酶法提取工艺优化及精炼对其品质的影响Optimization of enzymatic extraction process for horse oil and effect of refining on its quality - 孙龙珠1，王颖1，CHISORO Prince1,2，曹克涛3，郭玉杰1，张春晖1SUN Longzhu1, WANG Ying1, CHISORO Prince1,2, CAO Ketao3, GUO Yujie1, ZHANG Chunhui1 (Zhongguo youzhi)
为提高马油的提取率及品质，以新疆马脂肪为原料，采用酶法提取马油。以马油提取率为考察指标，在单因素实验的基础上，通过响应面法优化马油的酶法提取工艺条件，并通过脱胶、脱酸、脱色对粗马油进行精炼处理，对比分析精炼前后马油的感官品质、理化指标和脂肪酸组成。结果表明：酶法提取马油的最佳工艺条件为选用中性蛋白酶、酶添加量2 000 U/g、料液比1∶ 2、酶解温度45 ℃、酶解时间2 h，在此条件下马油提取率为81.69%；精炼后马油的色泽、气味等感官指标明显改善，酸值（KOH）由1.13 mg/g降至0.92 mg/g，过氧化值由0.75 mmol/kg降至0.63 mmol/kg，碘值由81.14 g/100 g升至88.95 g/100 g，不饱和脂肪酸含量升高了3.1%。综上，采用中性蛋白酶酶法提取马油能有效提升马油提取率，且精炼后马油品质更佳。 In order to improve the extraction rate and quality of horse oil, Xinjiang horse fat was used as raw material to extract horse oil by enzymatic method. With the extraction rate of horse oil as the index, on the basis of single factor experiments, the process conditions of enzymatic extraction for horse oil were optimized by response surface methodology.The crude horse oil was refined by degumming, deacidification and decolorization, and the changes of sensory quality, physicochemical indexes and fatty acid composition of horse oil before and after refining were compared. The results showed that the optimal extraction conditions of horse oil were obtained as follows: neutral protease dosage 2 000 U/g, solid-liquid ratio 1∶ 2, enzymatic hydrolysis temperature 45 ℃, enzymatic hydrolysis time 2 h. Under these conditions, the extraction rate of horse oil was as high as 81.69%. The sensory indexes such as color and odor of horse oil were significantly improved after refining. The acid value decreased from 1.13 mgKOH/g to 0.92 mgKOH/g, the peroxide value decreased from 0.75 mmol/kg to 0.63 mmol/kg, and the iodine value increased from 81.14 g/100 g to 8895 g/100 g, and the unsaturated fatty acid content increased by 3.1%. In conclusion, extraction of horse oil using neutral protease could effectively improve the extraction rate of horse oil, and the quality of horse oil is better after refining.